Implementation of Independent Learning Curriculum in Social Studies Learning: Literature Review - Huldiya Syamsiar; I Wayan Lasmawan; I Gusti Putu Sudiarta (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
The curriculum plays an important role in determining the quality of learning. Changes to the education curriculum in Indonesia have occurred 11 times. Every curriculum change always begins with a study of the weaknesses of the current curriculum, then a comprehensive solution search process is carried out. In addition, curriculum changes can also occur because the existing curriculum does not accommodate scientific developments, developing cultural trends and other factors. Because of the importance of the role of the curriculum, it has become commonplace for researchers who focus on education to conduct studies which can be in the form of studies to determine the quality of the curriculum. The purpose of this study was to find similarities and differences in the study of self-learning curricula in social studies learning. In this writing, the data collection technique is through searching the Google Scholar database. In addition, the authors have used inclusion criteria in screening these papers. The results showed that social studies teachers' perceptions of the self-learning curriculum showed a positive trend even though several obstacles were found. From the effectiveness of the independent learning curriculum on social studies learning outcomes it is known that the Merdeka Learning curriculum gives satisfactory results, it is shown that students experience increased speaking skills and teamwork in groups.